PERAN AUDIT FORENSIK DALAM UPAYA PEMBERANTASAN KORUPSI DI INDONESIA - Astuti, Ni Putu Sri (Jurnal Akuntansi AKUNESA, 2013)
Fraud measures are classified into three groups, which is corruption, assets misappropriation, and fraudulent of financial statements. Cases of corruption is not a strange thing, especially in Indonesia, many cases of corruption and occur in almost every area. This article aims to explain the role of the forensic audit in the fight against corruption. Combating corruption is an important goal to achieve good governance that is free from corruption, collusion, and nepotism. One of the government's efforts in fighting corruption is through a forensic audit. Forensic audit emphasizes the process of finding evidence and proof of conformity assessment with the size of proof required in legal proceedings. Keywords : audit forensic, fraud, corruption, good governance